POTENSI EKOWISATA BERBASIS BUDAYA MASYARAKAT DI DESA SANARU, KABUPATEN LOMBOK UTARA - Purwana, Bambang H. Suta (Kebudayaan, 2018)
AbstractRinjani Mountain has been determined by government of West Nusa Tenggara as the Rinjani geopark and tourism destination using ecotourism of community based tourism. Throughecotourism of caommunity based tourism, the tourism, activities will involve participation of community and can provide economic benefits to the community. This article aims to answer the questions of what kinds of tourism potency to develop in supporting ecotourism development in Senaru village? What kind of policy of ecotourism has been implemented in tourism involving traditional society in Senaru village? The aim of this article is to know development of tourism potential and involvement of indigenous people in Senaru Village. The method that used in the study was literature study, observation, and interview to government official, tourism organizer, and prominent figures among society in Bayansubdistrict. The result shows that the managing of tourism in Rinjanu Mountain did not involve people surrounding in Senaru village. Thousands of tourists from abroad and domestic came and stayed in hotels, villas, and home stays in Senary village, but sociallyand economically it did not benefit to traditional society in Senaru village. Keywords: ecotourism, natural preservation, local culture preservation.AbstrakGunung Rinjani oleh Pemerintah Provinsi Nusa Tenggara Barat ditetapkan sebagai Geopark Rinjani sekaligus destinasi wisata dengan konsep ekowisata berbasis masyarakat (communitybased tourism). Dengan konsep ini kegiatan kepariwisataan akan melibatkan peran serta masyarakat dan dapat memberi manfaat ekonomi bagi masyarakat. Artikel ini dimaksudkan untuk menjawab pertanyaan, apa saja potensi wisata yang dapat dikembangkan untuk menunjang pengembangan ekowisata di Desa Senaru? Apakah kebijakan ekowisata sudah diimplementasikan dalam pengelolaan pariwisata yang melibatkan masyarakat adat Desa Senaru? Tujuannya mengetahui pengembangan potensi wisata dan pelibatan masyarakat adat di Desa Senaru. Metode yang digunakan dalam kajian ini adalah studi literatur, pengamatan, dan wawancara terhadap aparat pemerintah, pelaku wisata, dan sejumlah tokoh masyarakat di Kecamatan Bayan. Temuan dari studi ini adalah pengelolaan pariwisata di Gunung Rinjani tidak melibatkan masyarakat adat di Desa Senaru. Ribuan wisatawan manca negara dan wisatawan Nusantara datang silih berganti menginap di hotel, villa dan penginapan di Desa Senaru namun secara sosial dan ekonomi tidak memberikan manfaat bagi masyarakat adat Desa Senaru.